A Qualitative Study of Minnesota Nonprofit Hospital Social Workers’ Provision of Financial Assistance - Hannah MacDougall; Melissa Latcham (Health & Social Work, 2026)
Abstract The purpose of this study was to qualitatively explore the role of hospital social workers in the provision of nonprofit hospital financial assistance. Financial assistance (often known as “charity care”) could serve as an intervention to reduce medical debt. This exploratory, cross-sectional, semistructured qualitative interview study of a convenience sample of licensed hospital social workers in Minnesota was conducted virtually from September 2024 to January 2025. Interview data were collected from 18 licensed social workers employed by nonprofit hospitals/health systems in Minnesota. Interview recordings were transcribed, coded, and analyzed using thematic analysis. This study identified four key themes: (1) the importance of role delineation between hospital social workers and financial counselors, (2) difficulty finding financial assistance information, (3) difficulty understanding financial assistance information, and (4) fatigue/overwhelm experienced by patients and families navigating the financial assistance process. This research illuminates the method of providing financial assistance in nonprofit hospitals in Minnesota and identified strengths and weaknesses in the current process.